Penyalahgunaan Akun Netflix Oleh Pihak Kedua Di Media Sosial Di Tinjau Dari Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta dan Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Tatu Afifah; Rai Indah Nurhidayah (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2025)
One of the social media platforms that is currently widely used for buying and renting various objects is the Instagram application. With the large number of products available, including accounts for premium applications like Netflix, there are instances of social media accounts engaging in abuse by selling or renting out premium application programs on Instagram, such as the account named